2016
DOI: 10.1089/aid.2015.0191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 96 Weeks of Rosuvastatin on Bone, Muscle, and Fat in HIV-Infected Adults on Effective Antiretroviral Therapy

Abstract: Heightened inflammation and immune activation are associated with lower bone mineral density (BMD) and lean body mass (LBM) among HIV-infected persons. We hypothesized that a reduction in inflammation with rosuvastatin would be associated with improvements in BMD and LBM. HIV-infected participants on stable antiretroviral therapy without statin indication and with heightened immune activation ( ‡19% CD8T cells) or inflammation (hsCRP ‡2 mg/liter) were randomized to rosuvastatin 10 mg daily or placebo for 96 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…A recent clinical trial involving 72 PLWH demonstrated a modest 48-week relative increase in trochanter BMD (0.9%; 95% CI, À0.9-0.6%) and total hip BMD (0.6%; 95% CI, 0.0-1.1%) in the rosuvastatin arm that was significantly greater than the effect observed with placebo (P < 0.05) [45 & ]. However, despite the promising results at week 48, data at week 96 did not find differences in BMD between rosuvastatin and placebo groups [46]. These findings with rosuvastatin are in line with studies failing to show a conclusive direct association between increased inflammation and loss of BMD in PLWH [47].…”
Section: New Osteoporosis Strategies In People Living With Hivmentioning
confidence: 59%
“…A recent clinical trial involving 72 PLWH demonstrated a modest 48-week relative increase in trochanter BMD (0.9%; 95% CI, À0.9-0.6%) and total hip BMD (0.6%; 95% CI, 0.0-1.1%) in the rosuvastatin arm that was significantly greater than the effect observed with placebo (P < 0.05) [45 & ]. However, despite the promising results at week 48, data at week 96 did not find differences in BMD between rosuvastatin and placebo groups [46]. These findings with rosuvastatin are in line with studies failing to show a conclusive direct association between increased inflammation and loss of BMD in PLWH [47].…”
Section: New Osteoporosis Strategies In People Living With Hivmentioning
confidence: 59%
“…It must be noted, however, that other studies have not shown a mortality benefit with statin use (Overton et al, 2013;Krsak et al, 2015;Rasmussen et al, 2013). Statin therapy has also not been shown to reduce bone loss in a randomized trial of HIV-positive subjects receiving suppressive ART (Erlandson et al, 2016). Of note, retrospective studies have not shown a benefit of statin therapy for CVD risk reduction (e.g., myocardial infarction, stroke) among individuals on stable ART (Overton et al, 2013;Krsak et al, 2015).…”
Section: Ongoing Research On Chronic Inflammationmentioning
confidence: 97%
“…In addition, the 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitor (statin) simvastatin has been shown to increase osteoblast activity and decrease osteoclastogenesis, and is associated with increased fracture healing in in vivo animal models [124], while pravastatin has been shown to prevent PI-induced senescence in MSCs and restore osteoblastic potential in vitro [89]. Clinically however, in HIV-infected individuals on stable cART who had heightened immune activation, treatment with rosuvastatin for 96 weeks was not associated with any changes in BMD, although it was associated with improvement in lean body mass [125]. More data on the BMD effects of these medications in HIV-infected patients are needed.…”
Section: Management Of Hiv-associated Bone Lossmentioning
confidence: 99%